The potential of serum elabela levels as a marker of diabetic retinopathy: results from a pilot cross-sectional study - Muhammed Seyithanoğlu; Selma Meşen; Aysegul Comez; Ali Meşen; Abdullah Beyoğlu; Yaşarcan Baykişi; Filiz Alkan Baylan (PeerJ)
Background The aim of this study is to examine the relationship between elabela (ELA), a recently identified peptide also known as Toddler and Apela, and diabetic retinopathy (DR). ELA, produced in various tissues, acts as a natural ligand for the apelin receptor (APJ). Upon reviewing the existing literature, only one study was found investigating ELA, one of the APJ ligands, in the pathogenesis of DR. Methods In our study the patient group comprising individuals diagnosed with type 2 diabetes mellitus (DM), categorized into three subgroups based on detailed fundus examination: those without DR (non-DR) (n = 20), non-proliferative DR (NPDR) (n = 20), and proliferative DR (PDR) (n = 20). A control group (n = 20) consisted of individuals without DM. Blood samples were collected during outpatient clinic admission to measure serum ELA levels, which were determined using a commercial ELISA kit. Results The age, sex, and body mass index of the between groups were similar (p = 0.905, 0.985 and 0.241, respectively). The HbA1c levels of the between DM subgroups were similar (p = 0.199). Serum ELA levels were 217.19 ± 97.54 pg/mL in the non-DR group, 221.76 ± 93.12 pg/mL in the NPDR group, 302.35 ± 146.17 pg/mL in the PDR group and 216.49 ± 58.85 pg/mL in the control group. While ELA levels were higher in DM patients compared to the control group, this elevation did not reach statistical significance. Further analysis dividing DM patients into subgroups (non-DR, NPDR, and PDR) revealed higher ELA levels in the PDR group compared to the other subgroups, but this increase was not statistically significant. Conclusion Despite the absence of a significant difference in our study, the identification of elevated ELA levels in the PDR group offers valuable insights for future investigations exploring the association between DR and ELA.